Introduction: Organizational Innovation - David Stark (Sociologica)
This paper introduces a FOCUS Section on Organizational Innovation, including eight papers presented at COI@25, a conference celebrating the 25th Anniversary of the Center on Organizational Innovation at Columbia University in New York City on November 8–9, 2024.